Modeling of the communication link for data correction in network-rtk - Musa, Tajul Ariffin; Setan, Halim; Ses, Shahrum; Abdullah, Khairul Anuar; M., Arief (2008)
The current communication in several network-RTK systems is frame relay technology that applied packet switching network (leased line) based on IPVPN which services data transmission between reference stations to control station. The most significant shortcoming of frame relay technology is depend on cabling networks and bandwidth limitation that is not effective for the rural or suburban area. In other hand the channel speed of frame relay is relative small for data transmission. This limitation has an effect on bandwidth, cost and time delay of the data transmission. In this paper we propose the system model of the 3G technology that is capable to overcome cabling dependency due to complicated installation, cost and time delay due to low data rate that will be applied for Network-RTK system in Metro-Area of Iskandar Malaysia. 3G technologies offer users a wider range of more advanced services while achieving greater network capacity through improved spectral efficiency. Services include widearea wireless voice telephony, video calls, and broadband wireless data, all in a mobile environment. It can be expected by applying of 3G technology in network-RTK, the performance system of real time data transmission are improved in bandwidth capacity, channel speed and diminish the expenditure of cablinginstallation.